Late-Onset Focal Epilepsy: Electroclinical Features and Prognostic Role of Leukoaraiosis - Tartara, Elena; Micalizzi, Elisa; Scanziani, Sofia; Ballante, Elena; Paoletti, Matteo; Galimberti, Carlo Andrea (Frontiers in Neurology, 2022)
The aim of this study was to describe the electroclinical and prognostic characteristics, and to investigate the role of leukoaraiosis in outpatients with new-onset elderly focal epilepsy aged ≥60 years, referred to a tertiary epilepsy center between 2005 and December 31, 2020. Among the 720 patients who were referred to the center, we retrospectively selected 162 consecutive outpatients, with a first referral for recent-onset focal epilepsy of unknown cause (UC) or structural cause (SC), and collected a clinical and standard-Electroencephalogram (S-EEG), 24-h ambulatory EEG (A-EEG), and neuroimaging data. We also analyzed the seizure prognosis after titration of the first antiseizure medication (ASM). One hundred and four UC and 58 SC patients, followed up for 5.8 ± 5.3 years (mean ± SD), were included. Compared with the SC group, the patients with UC showed a predominance of focal seizures with impaired awareness (51.9% of cases) and focal to bilateral tonic-clonic seizures during sleep (25%); conversely, the SC group, more frequently, had focal to bilateral tonic-clonic seizures during wakefulness (39.6%) and focal aware seizures (25.8%) (p < 0.0001). Oral or gestural automatisms were prevalent in UC epilepsy (20.2 vs. 6.9% in the SC group, p = 0.04). In UC compared to patients with SC, interictal epileptiform discharges showed a preferential temporal lobe localization (p = 0.0007), low expression on S-EEG, and marked activation during deep Non-Rapid Eye Movement (NREM) sleep (p = 0.003). An overall good treatment response was found in the whole sample, with a probability of seizure freedom of 68.9% for 1 year. The cumulative probability of seizure freedom was significantly higher in the UC compared with the SC group (p < 0.0001). The prognosis was worsened by leukoaraiosis (p = 0.012). In the late-onset focal epilepsy of unknown cause, electroclinical findings suggest a temporal lobe origin of the seizures. This group showed a better prognosis compared with the patients with structural epilepsy. Leukoaraiosis, per se, negatively impacted on seizure prognosis.